A Review of Teaching and Learning Linguistic Politeness - Wong , Leei; Esler , Joshua (Journal of Critical Studies in Language and Literature, 2020)
Research on politeness has flourished since Brown and Levinson's (hereafter B&L) classical (1978, 1987) definition of politeness theory, and has extended to current research on impoliteness. However, there is a knowledge gap in the area of Teaching and Learning Politeness (hereafter TLP) in second language acquisition.This paper aims to identify this gap, by tracing the roots of research on TLP since 1975, to explore how past research has impacted current trends, and then focuses on the position and relevance of TLP in the local Australian curriculum, in the area of intercultural competency, benchmarked in reference to the Common European Framework of Reference (CEFR). The synthesis of the literature in this paper will elicit the challenges in TLP and potentially result in a clearer direction in the area of second-language research on politeness.